Same degrees, different outcomes? Fields of study choices and gender wage inequality in Finland and Germany - Hägglund, Anna Erika (Elsevier, 2025)
Men and women's diverging fields of study choices contribute to the gender wage gap among highly educated workers in several countries, yet systematic cross-national comparisons are rare. Using data from the German Socio-Economic Panel Study, the German Microcensus, and Statistics Finland this study explores whether fields of study shape the gender wage gap differently in Germany than in Finland; two countries that display strong linkages between education and employment, but differ in the generosity of family policies. The results show that fields of study are an important source of gender wage disparities in both countries. In Germany, associations between characteristics of fields and wages do not seem to differ between the genders. In Finland, the findings suggest that women profit more than men from fields with strong linkages to occupations. Our findings highlight that research analyzing the association between fields of study and gender inequality needs to consider institutional features and gender-specific patterns.